MENGOPTIMALKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING KOMBINASI REALISTIC MATEMATIC EDUCATION, SNOWBALL THROWING - Humaera; Darmiyati (STKIP Subang, 2025)
The main problem of this study was the low level of student activity, critical thinking, and mathematics learning outcomes, particularly in whole number division. These challenges arose from limited student engagement, underdeveloped thinking skills, and results that fell below the Minimum Mastery Criteria. To address this, the study applied a combination of the Problem-Based Learning model, Realistic Mathematics Education, and Snowball Throwing. The research aimed to describe teacher and student activities, analyze students’ critical thinking skills, and evaluate their learning outcomes.This study used a Classroom Action Research (CAR) design with fourth- grade students of class IVB at SDN 5 Loktabat Banjarbaru in the 2024/2025 academic year as subjects. Both qualitative and quantitative approaches were employed. Qualitative data were gathered through observations of teacher and student activities, while quantitative data were obtained from student learning outcomes based on Final Semester Assessment (SAS) scores. Data were analyzed using percentage scales and predetermined indicators of success.The findings indicated that in the final cycle, teacher activity reached the “Excellent” category, student activity was “Highly Active,” and critical thinking skills were categorized as “Highly Skilled.” Furthermore, classical mastery of learning outcomes met the expected criteria. In conclusion, the integration of Problem-Based Learning with Realistic Mathematics Education and Snowball Throwing effectively improved student participation, critical thinking, and mathematics achievement in whole number division. This model is recommended as an alternative for teachers to enhance engagement, foster critical thinking, and improve academic results in mathematics and other related subjects.